A Placement and Sizing of Distributed Generation Based on Combines Sensitivity Factor and Particle Swarm Optimization: A Case Study in Bali’s Power Transmission Networks - Ngakan Putu Satrya Utama; Rukmi Sari Hartati; Wayan Gede Ariastina; Ida Bagus Alit Swamardika (International Journal of Engineering and Emerging Technology, 2017)
Although many methods for optimizing DGplacement and its size in a network with the target of reducingsystem power losses and voltage profile have already beencommended, they still lack from several weaknesses. As a resultmuch can be done about to happen with new algorithms. Theproposed algorithms commonly have stressed their formulationson real power losses only and ignored the reactive power losses.Power systems reactive power injection plays an important rolein voltage stability control, thus the reactive power losses need tobe incorporated in optimizing DG allocation considering theirvoltage profile improvement. Whereas Particle SwarmOptimization (PSO) approach was proposed for finding theoptimal size of DG. This study work intended to apply both realand reactive power flow, power loss sensitivity factors and PSOmethod in finding the candidate buses for DG placement and itssize on Bali’s 150 kV transmission networks. The experimentalresults show that the proposed algorithm is indeed capable ofobtaining a good quality solution efficiently